Impact of Organizational Communication Strength on Employee Engagement: The Mediating Role of Perceived Supervisor Support and Moderating Role of Organizational Trust - DR. MUZAMMEL SHAH; DR. MUZAMMEL SHAH; DR. MUZAMMEL SHAH (Journal of Business & Tourism, 2021)
Companies need employees who are passionate about their job and strive to take organization to height of glory.Owing to high competition in banking sector, it is pertinent to note that banks need to differentiate themselves from competitors. The objective of this study was to examine the relationship of organizational communication strength and employee engagement, with mediating effect of perceived supervisor support and moderating role of organizational trust. Data was collected from a sample 244 employees of banking sector who were through simple random sampling. Cronbach’s alpha was used to test the reliability of the scales used in the study. Correlation and regression analyses were used to analyze the hypothesized relationships. The findings revealed a significant positive relationship between communication strengthand employee’s engagement. Perceived supervisor support mediated the relationship ofcommunication strength and employee’s engagement. Organizational trust moderated the relationship of Perceived supervisor support and employee’s engagement. Organizations should focus on promoting a strong communication system to increase the dedication, vigor and absorption of employees.